Traumatic Temporomandibular Joint Luxation in a Cat and Treatment by Condylar Tethering - Caporn, T. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
The cat in this report was admitted with mandibular symphyseal separation and jaw malocclusion referrable to luxation of the right TMJ. Radiographs revealed a fracture of the right articular eminence in the frontal plane of the head. Closed reduction, while initially successful, failed to prevent reluxation of the mandible. Polyester suture was used to successfully tether the right mandibular condyle to the zygomatic process of the temporal bone, preventing any reluxation and allowing healing of the fractured eminence.Temporomandibular joint (TMJ) luxation is a relatively commonly encountered injury of the feline jaw. While most temporomandibular joints remain stable once relocated, some will reluxate. A new technique using polyester suture to successfully treat an unstable rostral TMJ luxation, and associated fracture in a cat, is described. Alternative treatments for this condition are briefly discussed.
Keywords: Traumatic luxation; temporomandibular joint luxation; condylar tethering